Impaired hemodynamic forces assessed by routine CMR and its determinants in different duration T2DM patients with normal LV function and myocardial strain - Guozhu Shao; Guozhu Shao; Guozhu Shao; Yukun Cao; Yukun Cao; Yukun Cao; Yue Cui; Yue Cui; Yue Cui; Hongyan Li; Heshui Shi; Heshui Shi; et al. (Frontiers in Cardiovascular Medicine)
BackgroundEarly detection of subclinical myocardial dysfunction in asymptomatic patients with type 2 diabetes mellitus (T2DM) is essential before overt changes in left ventricular ejection fraction (LVEF) and myocardial strain occur. The objective of this study is to quantitatively assess hemodynamic forces (HDFs) using a rigorous mathematical model based on conventional cine cardiac magnetic resonance (CMR) images in patients with T2DM, and investigate their correlation with late gadolinium enhancement (LGE) and duration of diabetes.MethodsWe recruited 63 T2DM patients and 50 healthy volunteers to undergo contrast-enhanced CMR examinations. T2DM patients were divided into three groups according to the course of disease: early, middle and later stage (time <5 years, 5 ≤ time <10 years, time ≥10 years, respectively). LV deformation parameters, global circumferential strain (LVGCS), radial strain (LVGRS), longitudinal strain (LVGLS) and HDFs parameters such as longitudinal (apical-basal/A-B), transversal (lateral-septal/L-S) HDF strength (RMS) were measured and compared among the three groups.ResultsCompared with healthy volunteers, no significant differences in LV function and strains were observed (P > 0.05), while HDF Strength (RMS) L-S (%) were significantly higher in T2DM patients (p < 0.001). LVGLS was significantly decreased in late T2DM patients (p < 0.05), but HDF Strength (RMS) L-S (%) was significantly increased compared with early T2DM patients. Both HDF Strength (RMS) L-S (%) and HDF Strength (RMS) A-B (%) value were independently related to the extent of LGE (β = 0.435, p = 0.001; β = −0.329, p = 0.006, respectively). In addition, HDF Strength (RMS) L-S (%) was also independently correlated with insulin treatment(β = 0.291, p = 0.013).ConclusionsHDF analysis can provide valuable insights into subclinical myocardial dysfunction prior to changes in ejection fraction and myocardial strain, suggesting that HDF analysis may be a potential early marker of subclinical myocardial dysfunction. LVGLS damage is gradually obvious with the prolongation of diabetes duration in T2DM patients. HDFs parameters are associated with the extent of LGE, and the transversal component of HDF increased with the duration of diabetes.